Can changes in hoof wall temperature and digital pulse pressure be used to predict laminitis onset? - Brown, Honoria (Veterinary Evidence, 2019)
PICO question In horses and ponies at risk of laminitis, does the use of hoof wall temperature and digital pulse pressure as diagnostic techniques for acute laminitis provide a method of detecting acute laminitis in the prodromal stage? Clinical bottom line A palpable bilateral increase in forelimb hoof temperature maintained for longer than half a day may indicate that the horse is 18–24 hours from acute laminitis onset. A period of increased digital pulse may also be expected up to 11 hours prior to onset. Further studies using larger and more representative cohorts are required to confirm the accuracy of the times at which such changes can be expected.